CS–CNTs homojunctions prepared by in situ growth of carbon nanotubes on the surface of porous carbon spheres for lithium–sulfur batteries. (2nd September 2021) - Qi, Man; Liu, Yingxue; Li, Qing; Yu, Youchun; Gu, Jianmin; Bai, Zhitao; Yan, Shuxin; Wang, Liqiu; Liu, Yuwen
Abstract: Lithium–sulfur battery is expected to become a new generation of commercial battery owing to its ultra-high theoretical specific capacity, low-cost, and environmental benign. However, the inherent insulation of sulfur and the shuttle effect of lithium polysulfide between electrodes limit the application of lithium–sulfur battery. In order to solve these problems, we focus on the design of carbon–sulfur composite structure. Herein, CS–CNTs homojunctions featured with the carbon nanotubes (CNTs) in situ grown on carbon sphere (CS) is designed and synthesized by simple polymerization and heat treatment. The composites of CS with interconnected pore networks and CNTs with high conductivity not only offer a conductive framework to promote fast electron transmission, but also provide a larger space to load sulfur and effectively capture polysulfides. The CS–CNTs@S cathode shows better electrochemical performance compared with CS–CPs@S and CS@S. The first discharge specific capacity is 1053 mAh g −1 at 0.1 C. After 200 cycles, the specific capacity still remains at 427 mAh g −1 .